2002
DOI: 10.3917/spub.024.0403
|View full text |Cite
|
Sign up to set email alerts
|

Éducation à la santé à l'école : pratiques et représentations des enseignants du primaire

Abstract: A better understanding of primary school teachers' practices and representations toward health education (HE), and identification of individual or structural resistance as well as the partnership and training needs all constitute important goals in HE research. A quantitative study was conducted between April and December 2001 on a representative sample of the population of primary school teachers (n = 673) in the Auvergne region. The results demonstrate that the majority of teachers declare practicing and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 9 publications
0
6
0
10
Order By: Relevance
“…Apprentissage 4, 6,11,13,20,27 (n = 6) 1, 2,3,5,7,8,9,10,12,14,15,18,19,22,23,24,25,26 (n = 18) En fonction (de la pathologie) 16, 17, 21 (n = 3). Non-pertinent : 28, 29, 30 (n = 3) L'implication du patient dans la relation soignant-patient est plus fréquente dans la participation aux activités que dans les décisions qui fixent le cadre de ces activités.…”
Section: Enseignementunclassified
See 2 more Smart Citations
“…Apprentissage 4, 6,11,13,20,27 (n = 6) 1, 2,3,5,7,8,9,10,12,14,15,18,19,22,23,24,25,26 (n = 18) En fonction (de la pathologie) 16, 17, 21 (n = 3). Non-pertinent : 28, 29, 30 (n = 3) L'implication du patient dans la relation soignant-patient est plus fréquente dans la participation aux activités que dans les décisions qui fixent le cadre de ces activités.…”
Section: Enseignementunclassified
“…Les représentations sociales pourraient offrir une piste pour comprendre ces divergences. Le lien réciproque entre représentations et pratiques est établi expérimentalement [3,4] et de plus en plus étayé par des recherches sur le terrain [5][6][7][8] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Nous avons sélectionné ici les travaux les plus pertinents en lien avec notre champ d'étude (l'école primaire), mais le lecteur peut se référer à d'autres travaux pour ce qui concerne l'enseignement secondaire (Fiard, Jourdan, Simar et Bertin, 2008 ;Turcotte, Otis et Gaudreau, 2007) et, pour une approche plus large, à l'étude de St Leger (1998). Une étude quantitative par questionnaire réalisée en France (Jourdan, Piec, Aublet-Cuvelier, Berger, Lejeune, Laquet-Riffaud, Geneix et Glandier, 2002) montre que 71 % des enseignants déclarent aborder ces questions, essentiellement en référence à des approches thématiques (hygiène, alimentation…). Les principaux déterminants de ces pratiques sont le fait de travailler dans des zones prioritaires ou dans le cadre d'un regroupement pédagogique intercommunal, et le fait d'avoir reçu une formation.…”
Section: Contexte Théoriqueunclassified
“…A part of this curriculum is called "human body and health education" (MEN, 2002). A quantitative study of teachers' practices showed that teachers focus mainly on nutrition, hygiene, and dental health (Jourdan, & al., 2002). In the curriculum, the topic "Reproduction of living beings and sexuality education" concerns children aged 9-11 (Key Stage 2).…”
Section: Introductionmentioning
confidence: 99%